Internet of Things-Enhanced Healthcare Services - Das Adhikary, Bidisha (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) technology has attracted much attention in recent years for its potential to alleviate the strain on healthcare systems caused by an aging population and a rise in chronic illness. In IoT based healthcare, various distributed devices aggregate, analyze and communicate real time medical information to the cloud, thus making it possible to collect, store and analyze the large amount of data in several new forms and activate context based warnings. IoT has helped both practitioners and researchers to design innovative solutions in healthcare. The IoT-enabled healthcare research is significant due to its valuable inference, including higher quality and lower cost of services and reliable preventive care.